2014
DOI: 10.4314/gjl.v3i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Person Deixis as Discursive Practice in Nigeria’s “June 12” Conflict Rhetoric

Abstract: Drawing on the "June 12" political crisis in Nigeria, this study analyses the speeches of some political figures in the vanguard of the unprecedented power tussle between the military and civilians in Nigeria's political history between 1993 and 1998. The paper applies the tools of Critical Discourse Analysis to examine person deixis as a discursive strategy appropriated for ideological purposes in the power play. The study reveals that by deploying person deixis in the conflict rhetoric, the political figures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…In a similar study, Adegoju (2005) observed that political language, especially in conflict situations, is characterized by ideological and power positioning of the ‘we’, ‘our’, ‘ours’ and ‘us’ versus the ‘they’, ‘their’ and ‘them’ categories. Adegoju (2014) in his study of the 12 June 1993 Nigerian elections further notes that person deixis is a discursive strategy appropriated in the conflict rhetoric of political figures to control or shape the cognition and actions of their audiences.…”
Section: The Discourse Of Political Campaignsmentioning
confidence: 99%
“…In a similar study, Adegoju (2005) observed that political language, especially in conflict situations, is characterized by ideological and power positioning of the ‘we’, ‘our’, ‘ours’ and ‘us’ versus the ‘they’, ‘their’ and ‘them’ categories. Adegoju (2014) in his study of the 12 June 1993 Nigerian elections further notes that person deixis is a discursive strategy appropriated in the conflict rhetoric of political figures to control or shape the cognition and actions of their audiences.…”
Section: The Discourse Of Political Campaignsmentioning
confidence: 99%
“…The administration of General Babangida introduced policies like Structural Adjustment Programme (SAP) that are not healthy for Nigeria's economy. The administration conducted an election in 1993 which was worldly considered to be free, fair and credible, but the result of the election was annulled by General Babangida regime which resulted to mass protests and demonstration by Nigerians both at home and abroad (Adegoju, 2014). The regime later handed over power to Chief Ernest Shonekan as an interim government on 26th August, 1993.…”
Section: Historical Background Of Nigerian Foreign Policy and Africa'mentioning
confidence: 99%
“…Adegojul [1] studied the implementation of person deixis in the political discourse of Nigeria's "June 12" conflict. He believes that in addition to the referential function of deixis, they are used by politicians to establish and promote their Tahani Saleh Alabdali: Personal Deixis Implementation in King Fahad's Speech to the International Troops During the Second Gulf War (1990War ( /1991 ideological positions on specific issues.…”
Section: Previous Studiesmentioning
confidence: 99%